From CSR Beneficiaries to Community Water Enterprise: Institutionalizing KP SPAMS in Post Mining Clean Water Governance in Angsana Subdistrict, Tanah Bumbu, South Kalimantan, Indonesia - Tri Andi Subagiyo; Silvyna Aditia; I Komang Tri Febi Astawa; Arifah Farsyah Riyandini Gazali; Sandhy Rahmad Agustino (Cakrawala Repositori IMWI)
This article examines how a mining CSR-supported clean water program contributes to the emergence of a community-based water service institution in a post-mining context. Using the Andaru Mamulih Angsana Program implemented by PT Borneo Indobara in Angsana Subdistrict, Tanah Bumbu Regency, South Kalimantan, this study analyzes the institutionalization of KP-SPAMS Tirta Wangi and KP-SPAMS Tirta Lumintu Jaya as local clean water service managers. Rather than focusing solely on short-term aid delivery, the study explores how CSR programs can contribute to building local capacity for long-term service management. This study examines how the Andaru Mamulih Angsana Program institutionalizes community roles in post-mining clean water services through KP-SPAMS Tirta Wangi and KP-SPAMS Tirta Lumintu Jaya. It also investigates the role of Local Heroes as local institutional actors. The study applies a descriptive single-case study approach combined with document analysis. The primary data source is the 2024 Social Innovation Report of PT Borneo Indobara. The analysis draws on the concepts of co-production and community-based institutional entrepreneurship. The findings identify four institutional elements documented in the program: legal recognition, local organizational structures, financial arrangements, and shared social values. The report also indicates that Local Heroes function as intermediaries connecting the company, village government, and community members. The reported outputs demonstrate growth in household water connections, affordable tariffs, subsidy mechanisms, and documented program investment. These findings indicate early evidence of community-based service management. However, this study does not assess causal impacts; therefore, the findings should be interpreted as a document-based analysis that requires further field verification.